A graphene‐based tunable negative refractive index metamaterial and its application in dynamic beam‐tilting terahertz antenna. Issue 12 (5th August 2019) - Luo, Yanbin; Zeng, Qingsheng; Yan, Xin; Jiang, Tao; Yang, Rongcao; Wang, Jiayun; Wu, Yong; Lu, Qichao; Zhang, Xia
Abstract: Graphene is emerging as a kind of promising 2D material in designing reconfigurable terahertz (THz) devices owning to its tunability of the surface conductivity, which can be tuned by changing the chemical potential. In this work, we demonstrated a graphene‐based THz tunable negative refractive index metamaterial. The proposed metamaterial unit consists of a metallic resonant structure and embedded graphene, which presents a dynamic negative refractive index in the corresponding bands by modulating the chemical potential of the embedded graphene. In addition, a dynamic beam‐tilting antenna loaded with the metamaterial‐based stacked configuration has been designed. Through changing the refractive index of the metamaterial or the number of layers in the stacked configuration, the steering angle can be adjusted from 0° to −27°. This work demonstrates the great potential of graphene in THz tunable negative refractive index materials, provides a classic case about the practical application of controllable negative refractive index, and also gives an effective way to design dynamic beam‐tilting antenna.